PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMA NEGERI 1 BANUHAMPU KABUPATEN AGAM - Alman Sori; Sakdanur Nas; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to describe the effect of the principal’s leadership style on teacher performance at SMA Negeri 1 Banuhampu Agam Regency. This research is type of quantitative descriptive research. The population in this study were all teachers and teaching staff at SMA Negeri 1 Banuhampu Agam Regency. And the sample in this study were all 56 teachers. The sampling technique used was Total Sampling. The data collection technique used Questionnaire with a Likert Scale. Data analysis used descriptive analysisand simple regression analysis. The result of the this study indicate that the proncipal’s leadership style has a positive and significant effect on teacher performance. The t count for the principal’s leadership style variable is 3,140 and the t table is2,00488, thus t count > t table. This means that leadership style affects performance. The regression coefficient value is 0,402. The regression coefficient value is positive (+), so it can be said that leadership style (X) has a positive effect on teacher performance (Y).Key word: Leadership style, teacher performance